2000
DOI: 10.2307/3454388
|View full text |Cite
|
Sign up to set email alerts
|

Does the Risk of Childhood Diabetes Mellitus Require Revision of the Guideline Values for Nitrate in Drinking Water?

Abstract: In recent years, several studies have addressed a possible relationship benteen nitrate exposure and childhood type 1 insulin-dependent diabetes meilitus. The present ecologic study describes a possible relation between the incidence of type 1 diabetes and nitrate levels in drinking water in The Netherlands, and evaluates whether the World Health Organization and the European Commission stndard for nitrate in drinking water (50 mg/L) is adequate to prevent risk of this disease. During 1993During -1995 Even t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 5 publications
(9 reference statements)
2
8
0
Order By: Relevance
“…Simple relations were estimated using the c 2 test for a linear trend between SIRs and the thirds of the child population density and all other water chemicals. SIRs were calculated based on the thirds of all variables by dividing them into three strata, all with approximately equal childhood populations, as used in similar studies [24,28,29]. Nitrite was excluded from the analysis because more than 95% of the nitrite samples (2895 of 3043) had only one value (0.01 mg/l).…”
Section: Methodsmentioning
confidence: 99%
“…Simple relations were estimated using the c 2 test for a linear trend between SIRs and the thirds of the child population density and all other water chemicals. SIRs were calculated based on the thirds of all variables by dividing them into three strata, all with approximately equal childhood populations, as used in similar studies [24,28,29]. Nitrite was excluded from the analysis because more than 95% of the nitrite samples (2895 of 3043) had only one value (0.01 mg/l).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, several investigators have described a possible relation between nitrate exposure and incidence of diabetes mellitus (Van Maanen et al 2000;Marienfeld et al 2007;Ghasemi and Zahediasl 2013). Diabetes mellitus is a pathologic condition resulting in severe metabolic imbalance.…”
Section: Discussionmentioning
confidence: 99%
“…Drinking water is the most common pathway through which population is exposed to nitrate (Van Maanen et al 2000). Studies in this field provided evidence for the association between incidence of diabetes and nitrate in drinking water at concentrations above or less than WHO level of 50 mg/ L (Van Maanen et al 2000). In this concern, most of the studies have focused on the incidence of diabetes in the adult population (Ghasemi and Zahediasl 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Parslow et al (32) reported that the rate of diabetes was 30% higher among those in water supply zones with average nitrate levels of 14.9-40 mg/L compared with those in areas with means less than 3.2 mg/L. Van Maanen et al (33) reported a 50% increase in rates when nitrate levels exceeded 25 mg/L, compared with levels less than 10 mg/L, though the confidence interval (CI) for this increase was wide and included one. The average nitrate concentrations in all areas of all three studies were below the current World Health Organization standard (50 mg/L) (34).…”
Section: Nitrates Nitrites and Nitrosoaminesmentioning
confidence: 99%